1953
DOI: 10.2134/agronj1953.00021962004500050009x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of Weeds and Accompanying Crop Plants1

Abstract: EED control is one of the most important and expenw s i v e operations in crop production. Basic information about weeds is important to the research worker as well as to the practical farmer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
2

Year Published

1978
1978
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 3 publications
3
36
0
2
Order By: Relevance
“…In weedy treatments, 37.5 kg N, 11.6 kg P and 38.3 kg K/ha were depleted in comparison to full-season weed-free conditions. The results are in conformity with the findings of Vengris et al, (1953), who reported vigorous growth and higher biomass of weeds resulted in more nutrient depletion.…”
Section: Nitrogen Uptake By Crop and Weedssupporting
confidence: 92%
“…In weedy treatments, 37.5 kg N, 11.6 kg P and 38.3 kg K/ha were depleted in comparison to full-season weed-free conditions. The results are in conformity with the findings of Vengris et al, (1953), who reported vigorous growth and higher biomass of weeds resulted in more nutrient depletion.…”
Section: Nitrogen Uptake By Crop and Weedssupporting
confidence: 92%
“…In general weeds have more aggressive nutrient uptake compared to crops (Vengris et al, 1953), therefore altering timing, placement, and source in order to preferentially provide the crop with better access to nutrients is desirable. In soils with low background levels of fertility, banding of fertilizers can reduce weed biomass compared to broadcasting, with deep banding being more effective than surface banding (Di Tomaso, 1995;Liebman and Mohler, 2001;Derksen et al, 2002).…”
Section: Spatial Arrangement Of the Cropmentioning
confidence: 99%
“…Le chénopode est une plante qui consomme beaucoup d'éléments nutritifs, plus particulièrement l'azote, le potassium, le calcium, le magnésium et le fer (Ervio 1971;Shahi 1978;Vengris et al 1955). D'après Malicki et Berbeciowa (1986), les contenus en N, P, K, Ca, Mg et Na sont plus élevés dans le chénopode que dans le blé, ce qui en fait un fort compétiteur pour les éléments nutritifs.…”
Section: Résultats Et Discussionunclassified